Exploring land use conflicts arising from economic activities and their impacts on local communities in the European Arctic - Živojinović, Ivana; Elomina, Jerbelle; Pülzl, Helga; Calanasan, Karen; Dabić, Isidora; Ólafsdóttir, Rannveig; Siikavuopio, Sten; Iversen, Audun; Robertsen, Roy; Bjerke, Jarle; Engen, Sigrid; Tommervik, Hans; et al. (Taylor & Francis, 2024)
The European Arctic is commonly thought of as a pristine and homogeneous area. In reality, it is a diverse region experiencing growth relying on natural resource extraction. Despite local communities being primarily affected by industry activities, most socioeconomic impact assessments are conducted at the macro level. This study addresses this gap by examining the impacts of economic activities on local communities. Using secondary data and semi-structured interviews from 15 hubs in five European Arctic countries, the study draws on locally relevant insights. Findings indicate that many activities focus on economic growth, and existing strategies do not adequately address biophysical boundaries. Furthermore, alternative activities need to be developed in a more balanced manner that aligns with the needs of indigenous and local communities. Finally, participation of various actors in future developments is critical to reduce the negative impacts of industry activities.
Keywords: land use conflicts; forestry; indigenous peoples; extractive industries; tourism